FENOMENA BULLYING DAN UPAYA PREVENTIF UNTUK MEMINIMALISIR PSIKOLOGISNYA BAGI MAHASISWA BP 2023 PRODI PENDIDIKAN GEOGRAFI STKIP PESISIR SELATAN - Rahayu, Intan Dwi; Veni, Veni; Yanto, Andri; Sefrinal, Sefrinal; Nazmai, Yanti; Ramadhani, Ramadhani; Oktamalasendi, Unik (STKIP Pesisir Selatan, 2024)
The phenomenon of bullying leaves quite a lasting psychological impact and seems to be a nightmare for a person's life, especially for victims, especially those who do not have good social adjustments and are rather slow in adapting to their environment. The negative impact experienced by someone who has been a victim of bullying is the main locus and becomes an accentuation and will be elaborated more deeply by researchers. This type of research is qualitative research carried out by observing phenomena that often occur in the campus environment. At least policy holders are able to provide strategic steps as a form of adult responsibility for the psychological and academic development of the nation's future generation. This type of research is qualitative research carried out by observing phenomena that often occur in the campus environment, linked to existing theories as a result of previous research and will be explained in descriptive form. The results of this research are an applicable form of preventing bullying in the campus environment, considering that the campus is one of the laboratories producing Indonesia's next generation.